2017
DOI: 10.1038/s41598-017-02798-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic roles of microRNAs in hepatocarcinogenesis: A study of thioacetamide with multiple doses and time-points of rats

Abstract: Environmental chemicals exposure is one of the primary factors for liver toxicity and hepatocarcinoma. Thioacetamide (TAA) is a well-known hepatotoxicant and could be a liver carcinogen in humans. The discovery of early and sensitive microRNA (miRNA) biomarkers in liver injury and tumor progression could improve cancer diagnosis, prognosis, and management. To study this, we performed next generation sequencing of the livers of Sprague-Dawley rats treated with TAA at three doses (4.5, 15 and 45 mg/kg) and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Overexpression of miR-455-3p inhibited tumour growth in prostate cancer 31 and renal carcinoma cells 32 . In a rat model of thioacetamide-induced hepatocellular carcinoma, decreased expression of miR-455-3p was detected during early stage of cancer development 33 . The same study also identified miR-34a-5p as an early marker for hepatocellular carcinoma although we did not detect any difference in miR-34a-5p between patients with or without LC (Supplementary Table S8 ).…”
Section: Discussionmentioning
confidence: 97%
“…Overexpression of miR-455-3p inhibited tumour growth in prostate cancer 31 and renal carcinoma cells 32 . In a rat model of thioacetamide-induced hepatocellular carcinoma, decreased expression of miR-455-3p was detected during early stage of cancer development 33 . The same study also identified miR-34a-5p as an early marker for hepatocellular carcinoma although we did not detect any difference in miR-34a-5p between patients with or without LC (Supplementary Table S8 ).…”
Section: Discussionmentioning
confidence: 97%
“…Some scholars have also found that TAA not only damages the liver of animals, but also affects the kidneys, brain, spleen, and bone of animals(Al-Bader et al 2000; Kleinfeld 1957;Lassila and Virtanen 1984b;Saran et al 2004). When the liver of animal model was treated by TAA, the enzyme metabolism of the liver, protein, adipose, amino acid and the messenger RNA were changed to varying degrees compared with the normal group (Dweep et al 2017;Fontana et al 1996;Nozu et al 1992;Okuyama et al 2005;Waters et al 2005). However, most scholars are concerned about the role of TAA in the liver and its mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some researchers pay attention to the reason of TAA caused liver damage, TAA mediated by microsomal CYP2E1 to TAA-S or S-dioxide that initiates cellular necrosis (Chilakapati et al 2005), Karantonis suggested that reducing the levels of reactive oxygen species may improve liver damage (Pallottini et al 2006), the platelet-activating factor had implicating participation in liver brotic process (Karantonis et al 2010). Then, other researchers explored how to inhibit TAA toxicity in liver, hepatic irradiation preconditioning enhances the effect of bone marrow-derived mesenchymal stem cell improving TAA-induced liver brosis in rats (Shao et al 2014), a study demonstrate that a small-molecule inhibitor of connexin 32 can protect against liver failure and death in wild-type mice when co-administered with TAA (Patel et al 2012), as well as miR-34a-5p that is microRNA was the most suitable early and sensitive biomarker for TAA-treated hepatic carcinoma (Dweep et al 2017). In addition, metabolic bone disease is common among patients with chronic liver disease (Compston 1986; Rouillard and Lane 2001), chronic liver disease is associated with alterations in receptor activator of nuclear factor kB ligand and osteoprotegerin serum levels, which could affect bone metabolism (Moschen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The data used in this analysis is reported from our lab ( Dweep et al, 2017 ) and available in the GEO repository (GSE87446) 1 . Briefly, thioacetamide was administered to rats for 3, 7, 14, and 28 days with 4.5, 15, and 45 g/kg, daily.…”
Section: Methodsmentioning
confidence: 99%